ADOLESCENT CRIMINAL SYSTEM, IMPUTABILITY AND RECIDENCE IN THE EDUCATIONAL CENTER OF THE MINOR OF CIUDAD DEL ESTE - Jaqueline Olmedo Hermosilla, Elva; Luisa Hermosilla de Olmedo, María (Revista Gênero e Interdisciplinaridade, 2022)
This research sought to determine the perception of adolescents and experts of the adolescent criminal jurisdiction about the incompetence of adolescents and their recidivism in the commission of punishable acts. The sample consisted of 15 adolescents admitted to the Educational Center for Minors, all male, to whom a questionnaire with open-ended questions was applied; 11 experts, to whom an ad hoc questionnaire was used, composed of single-choice items, including Likert scales; 1 authority of the Educational Center for Minors, who was interviewed with guiding questions. The analysis was carried out with the statistical package Excell. These analyzes have been descriptive. The investigation is completed by making observations regarding the care received by adolescents, the opinions obtained being very diverse, being that it is considered that internment does fulfill its function, which is to resocialize, however, others indicate that it worsens the situation. social of adolescents. Allowing to indicate in this way, that the recidivism in punishable acts committed by adolescents, in most cases is a consequence of not achieving resocialization.